"Desarrollar un modelo de gestión de inventario que permita regular el flujo de existencias en la ferretería Arias" - Sánchez Ayala, Ronald Alexander (2020)
This project is focused on the development of an inventory management model that allows the flow of merchandise in the Arias hardware store, located in the city of La Maná, which has a degree of inefficiency in the management and control of its inventories due to some measure, the lack of a system that allows to carry out a rigorous and detailed control as well as the inventory , suppliers, customers, and for this purpose a detailed analysis of the processes they develop in the company is carried out, where the poor management of their inventories is determined as the main factor which is why with the proposed system allows to keep control of all existing products improving their control, supply management, customers and suppliers, which guarantees a regulation of the flow of stocks. Key Words: Inventory management, management model, stock flow regulation, procurement